2019
DOI: 10.7717/peerj.7507
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose-derived stem cells overexpressing inducible nitric oxide synthase ameliorates diabetes mellitus-induced erectile dysfunction in rats

Abstract: Background Erectile dysfunction is a major complication of diabetes mellitus. Adipose-derived stem cells (ADSCs) have attracted much attention as a promising tool for the treatment of diabetes mellitus-induced erectile dysfunction (DMED). Inducible nitric oxide synthase (iNOS) plays an important role in protecting penile tissues from fibrosis. The aim of this study was to determine the efficacy of ADSCs overexpressing iNOS on DMED in rats. Methods ADSCs were isolated and infected with adenovirus overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Further, the type of stem cells used was autologous and allogenic, and the average number of stem cells injected per animal was 1 × 10 6 cells, which were delivered intra-cavernosally. However, the number of cells injected among these studies ranged from 2 × 10 6 to 5 × 10 5 cells per animal[ 46 , 47 ]. Moreover, in addition to stem cell therapy, several studies added growth factors, hormones and drugs, including insulin[ 48 ], magnetic iron oxide nanoparticles[ 49 ], microtissue[ 50 ], inducible NOS[ 47 ], myocardin[ 51 ], icariin[ 52 ], corin[ 53 ], exosomes from corpus cavernosum smooth muscle cells[ 54 ], fibroblast growth factor 2 (FGF2)[ 55 ], stromal cell-derived cell factor-1 (SDF-1)[ 56 ], VEGF[ 57 ] and hepatocyte growth factor[ 45 ].…”
Section: Stem Cells As a Future Therapy For Diabetic Edmentioning
confidence: 99%
“…Further, the type of stem cells used was autologous and allogenic, and the average number of stem cells injected per animal was 1 × 10 6 cells, which were delivered intra-cavernosally. However, the number of cells injected among these studies ranged from 2 × 10 6 to 5 × 10 5 cells per animal[ 46 , 47 ]. Moreover, in addition to stem cell therapy, several studies added growth factors, hormones and drugs, including insulin[ 48 ], magnetic iron oxide nanoparticles[ 49 ], microtissue[ 50 ], inducible NOS[ 47 ], myocardin[ 51 ], icariin[ 52 ], corin[ 53 ], exosomes from corpus cavernosum smooth muscle cells[ 54 ], fibroblast growth factor 2 (FGF2)[ 55 ], stromal cell-derived cell factor-1 (SDF-1)[ 56 ], VEGF[ 57 ] and hepatocyte growth factor[ 45 ].…”
Section: Stem Cells As a Future Therapy For Diabetic Edmentioning
confidence: 99%
“…As is known, oxidative stress is well recognized as a major pathogenic factor in the pathogenesis of DMED, which characterized by overproduction of ROS [33] and induces endothelial cell injury with the reduction of NO [34]. Numerous reports have indicated that NO plays a crucial role in the induction and maintenance of normal vascular physiology, is released from noncholinergic nerves and endothelium [16,35], and has been clarified that its bioavailability is decreased in the penis of human DMED patients [10,36]. The erectile response and maintain erection relies on the production of NO via nNOS initiates and eNOS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated stem cells showed typical broblast morphology when they were passed to the third CCSMCs were isolated from rat penis, as in our prior investigation [20]. The cells were then identi ed by immuno uorescence staining (Figure .…”
Section: Characterization Of Hucmscs and Ccsmcsmentioning
confidence: 67%
“…The capacity to develop into adipocytes and osteoblasts was then assessed using Oil red O and Alizarin red S staining. Our team's typical approach involved isolating corpus cavernosum smooth muscle cells (CCSMCs) from rat penis and purifying them using a differential adhesion method over the course of two weeks [20]. The CCSMCs were then grown in DMEM with 10% FBS added.…”
Section: Cell Identi Cation and Culturementioning
confidence: 99%